1998
DOI: 10.1159/000025307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Equine Infectious Anemia Virus Expression

Abstract: Equine infectious anemia virus (EIAV) is an ungulate lentivirus that is related to human immunodeficiency virus (HIV). Much of the understanding of lentiviral gene regulation comes from studies using HIV. HIV studies have provided insights into molecular regulation of EIAV expression; however, much of the regulation of EIAV expression stands in stark contrast to that of HIV. This review provides an overview of the current state of knowledge of EIAV regulation by comparing and contrasting EIAV gene regulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For instance, it has been reported that HIV-1 subtype E viruses replicate more efficiently than other subtypes in Langerhans cells, the possible target in heterosexual transmission (54), although follow-up studies could not confirm these results (16,43). The lentivirus equine infectious anemia virus provides an interesting example where the presence of an Ets-1 site in the LTR promoter was found to be essential for productive virus replication in macrophages (10,38). Despite accumulating sequence data on the genomes of HIV-1 strains belonging to the different subtypes (18,41), no subtype-specific differences in virus biology have been described.…”
Section: Fig 12mentioning
confidence: 99%
“…For instance, it has been reported that HIV-1 subtype E viruses replicate more efficiently than other subtypes in Langerhans cells, the possible target in heterosexual transmission (54), although follow-up studies could not confirm these results (16,43). The lentivirus equine infectious anemia virus provides an interesting example where the presence of an Ets-1 site in the LTR promoter was found to be essential for productive virus replication in macrophages (10,38). Despite accumulating sequence data on the genomes of HIV-1 strains belonging to the different subtypes (18,41), no subtype-specific differences in virus biology have been described.…”
Section: Fig 12mentioning
confidence: 99%
“…There is substantial variation in the LTR of different lentiviruses (Thompson, Elder, and Neil, 1994;Yamada et al, 1995) and evidence that differences in regulatory regions can affect phenotype. For example, acquisition of a transcription regulatory site can change tissue tropism and affect the level of virus production in a stimulated cell (Carvalho, Kirkland, and Derse, 1993;Maury, 1998;Tsichlis and Lazo, 1991). Further, there is subtype-specific variation in the HIV-1 LTR that affects viral replication in vitro (Jeeninga et al, 2000;Naghavi et al, 1999;van Opijnen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%